THE SPECIFIC CHARACTERISTICS OF PROMOTIONAL JOURNALISM – A COMPARATIVE ANALYSIS WITH OTHER RELATED CONCEPTS - CRINA ANIŞOARA TRIFAN (LICA) (Challenges of the Knowledge Society, 2013)
Purpose statement – This paper’s purpose is to contribute to the development of a specific know-how through the establishment of a theoretical framework of reference. This can facilitate the research steps which follow the identification; analysis; and interpretation of a new marketing instrument – promotional journalism. The objectives, of this study, relate not only to the establishment of theoretical but, also, to the practical characteristics, of promotional journalism. These are based on a comparative analysis with other related concepts and, also, on a qualitative analysis of the contents of the specific materials. Design – The research problem imposes a methodological interdisciplinary approach; this enables the identification; systematization; analysis; and theoretical interpretation of the fundamental concepts, theories and ideas, from the specialized literature, to be orientated towards studies and articles from separate fields. From the perspective of the research objectives and this interdisciplinary study of specilized literature, there was added a qualitative analysis of the content of the materials specific to promotional journalism found between 2002 and 2006, in the fashion magazine, Elle Romania. Overview - The specialized literature presented key-concepts; different terminologies; and meanings apparently for the same studied “reality“. This made the achievement of the process of conceptual delimitations even more difficult to the extent that promotional journalism was situated at the intersection of various sciences and the acknowledgment, of its related terms, were either similar or stated vaguely. Originality – This paper’s originality stems from the interdisciplinary perspective to the approach to the problematical aspect and the analysis and interpretitive complexity of the research results. These might prove useful both to the accomplishment of the studies in the field and for the practitioners and beneficiaries of this new marketing instrument.